The Role of TQM, Performance Measurement System, Reward System and Organizational Commitment to Improving Employee Performance - Pangaribuan, David; Nuryati, Tutty (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This research aims to examine the effect of Total Quality Management implementation, Performance of measurement system, Reward system and Organizational Commitment on Employee performance. Results of research showed that; the four independent variables have affect on employee performance. The research units are charman, vice charman, teachers and administrative staff of School Middle Rank, High Medium School, Special High Medium School of public schools and private schools in South Tangerang area. The research sample was 120 peoples, with using convenience sampling method. The research method using a quantitative approach was carried out in 2020. The implications of research on organizations is that they can improve employee performance through sustainably apply TQM principles. The performance measurement system provides important information in the form of input in improving the employee, performance measurement system for added value to the organization. The reward system is an employee performance motivation tool. Organizational commitment plays a role in improving performance. The limitations of the research are to link employee performance with the role of the management supervision system and the commitment to follow up on recommendations for improvement of internal auditors.